Employer Accounting for Pension Costs and Other Post-Retirement Benefits (Book). - Meyer, Philip E.; Hicks, Ernest L. (The Accounting Review, 1982)
Reviews the book "Employer Accounting for Pension Costs and Other Post-Retirement Benefits," by Harold Dankner, Michael P. Glinsky, John H. Grady, Murray B. Hirsch, and Richard M. Steinberg.